(untitled) (Global Journal of Science Frontier Research, 2022)
Biosensors is a type of devices that detect the biological signal and transfer to a measurable electrical signal. It encompasses the mixture of biological entities including deoxyribonucleic acid, ribonucleic acid, protein and enzyme based sensor to the electrochemical transducers to identify and perceive few biological analyte including Ab-Ag interaction. Some of the types includes, DNA and protein based biosensor materials have been pondered herein to highlight their obligatory uses in innumerable areas. The discovery of new diagnostic methods brings further attention to the implementation of point-of -care. This poses a big challenge for us to establish a novel material in electroanalytical approaches which can be precisely sensed animal studies. With the development of NT, biosensors depends on NMs are demonstrated enormous possibilities of more effectively diagnosing and detecting disease based biological markers. Further, Micro-Electro-Mechanical Systems (MEMS), high performance liquid chromatography (HPLC) and chip based analysis for DNA and protein are discussed in this article.